Validating product ideas : through lean user research - Sharon, Tomer, ....- (New York : Rosenfeld Media, 2016)
Want to know what your users are thinking? If you're a product manager or developer, this book will help you learn the techniques for finding the answers to your most burning questions about your customers. With step-by-step guidance, Validating Product Ideas shows you how to tackle the research to build the best possible product.